Identification and quantification of anthocyanins in the transgenic tomato - Su, Xiaoyu (Kansas State University, 2014)
Anthocyanins, a sub-class of flavonoids, are natural pigments derived from phenylpropanoid pathway. Most tomato cultivars found in nature have very low content of anthocyanins, but dark purple tomatoes by ectopic co-expression of two transcription factors Delila (Del) and Rosea1 (Ros1) from snapdragon and chalcone isomerase (CHI) from onion accumulated high levels of anthocyanins. This study is to identify and quantitate anthocyanins in these transgenic tomato lines. Seven anthocyanins including two new anthocyanins [malvidin-3-(p-coumaroyl)-rutinoside-5-glucoside and malvidin-3- (feruloyl) -rutinoside-5-glucoside] have been identified in transgenic lines by HPLC-MS. The top two anthocyanins are petunidin 3-(trans-coumaroyl)-rutinoside- 5-glucoside and delphinidin 3-(trans-coumaroyl)-rutinoside-5-glucoside that contribute for 85% of total anthocyanins in whole fruit. Comparing with undetectable anthocyanins in the wild type, Del/Ros1-expressing tomatoes contain total anthocyanins at 4.95±0.42 g/kg dry matter in whole fruit, 5.09±0.62 g/kg dry matter in peel, and 5.56±0.29 g/kg dry matter in flesh, while CHI×Del/Ros1-coexpressing tomatoes have 9.61±0.71 g/kg dry matter in whole fruit, 29.9±1.64 g/kg dry matter in peel, and 8.65±0.39 g/kg dry matter in flesh. No anthocyanins are detectable in the seeds of each line tested. Enrichment of tomato fruit with new and high anthocyanins may provide potential health-promoting benefits.
Keywords: Anthocyanins; Identification; Quantification; tomato; Food Science (0359); Nutrition (0570)